2022
DOI: 10.1002/cam4.4577
|View full text |Cite
|
Sign up to set email alerts
|

A novel signature based on immune‐related gene pairs and clinical features to predict prognosis and treatment effect in “driver gene negative” lung adenocarcinoma

Abstract: Objective Examining the role of immune‐related genes (IRGs) in “driver gene negative” lung adenocarcinoma (LUAD) may provide new ideas for the treatment and study for this LUAD subgroup. We aimed to find the hub immune‐related gene pairs can stratify the risk of “driver‐gene‐negative” LUAD. Materials and Methods IRGs were identified according to ImmPort database based on RNA sequencing results of tumors and normal tissues from 46 patients with “driver gene negative” LUAD at The First Affiliated Hospital of Sun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…[ 52 ] CMTM2 is one of immune-related genes and has a protective effect on some carcinomas. [ 18 ] Helicobacter pylori infection-related chronic inflammation is a leading cause of gastric cancer. [ 53 ] It has been reported that SJZ positively regulates innate immune response by increasing macrophages and is beneficial for gastrointestinal system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 52 ] CMTM2 is one of immune-related genes and has a protective effect on some carcinomas. [ 18 ] Helicobacter pylori infection-related chronic inflammation is a leading cause of gastric cancer. [ 53 ] It has been reported that SJZ positively regulates innate immune response by increasing macrophages and is beneficial for gastrointestinal system.…”
Section: Discussionmentioning
confidence: 99%
“…CMTM2 is an immune-related gene belonging to CMTM2 family and closely related to tumor progression, recurrence, and prognosis in lung cancer, hepatocellular cancer, and GC. [17][18][19] However, the role of CMTM2 in GC progression is not fully elucidated. In the present study, we found that SJZ treatment elevated CMTM2 mRNA and protein expression levels, and suppressed the proliferation, migration, invasion, and cancer stem cell-like properties of GC cells.…”
Section: Introductionmentioning
confidence: 99%
“… 9 , 10 It was found that immune-related gene pairs (IRGPs) can be used as predictors of LUAD prognosis. 11 , 12 However, the exact IRGs-associated pathways and mechanisms of immune cells in LUAD and how these genes affect the prognosis of LUAD remain unclear, which is worth further exploration.…”
Section: Introductionmentioning
confidence: 99%